CONTEMPORARY EXPERT DEBATES ON THE SCO-RELATED ISSUES - Denisov, I. E.; Safranchuk, I. A. (Vestnik MGIMO-Universiteta, 2016)
Since its establishment the SCO has always attracted a lot of expert attention. The SCO Forum was founded in 2006 to bring together for annual debates experts from all member-states. Within this format in-depth discussions took place in April 2016 in Dushanbe, which hosted this year conference of the SCO Forum. Participating experts and officials reviewed problems of security, economic cooperation (including transport and water-energy issues) and SCO enlargement, the latter being one of the most debatable. Experts presented some new thesis on all these problems, in particular on the enlargement issue. These new thesis are summed up in this article. Besides, the SCO Forum this year had many statements on the organization approaching a sort of new phase in its development. This line of discussions may lead in the future to even more active debates on SCO's role in the world. This article puts emphasis on the new elements of these debates and reviews major experts' attitudes within this line of discussion on the SCO being in front of a new stage of development.